Trypsin inhibitor activity in representatives of the genus Hedysarum (Fabaceae): the polyvariance of seasonal dynamics in Southern Siberia - E. V. Zhmud; N. S. Zinner; O. V. Dorogina (Труды по прикладной ботанике, генетике и селекции)
Background. Trypsin-inhibiting activity (TIA) is one of the factors of plant immunity. This factor provides the presence of general non-specific systemic resistance. Representatives of the genus Hedysarum L. are promising medicinal and high-protein fodder plants with high TIA in the leaves. High TIA values in the aboveground part of plants lead to a decrease in protein assimilation by animals. Therefore, identifying the differentiation in the features of TIA seasonal dynamics will make it possible to use the potential of these species most effectively under the conditions of Southern Siberia.Materials and methods. TIA in the leaves of mature generative plants of Hedysarum theinum Krasnob. and H. flavescens Regel & Schmalh. was analyzed. H. theinum is a rare species for Siberia; H. flavescens is a settled one in the forest-steppe zone of Western Siberia. The studies were conducted with H. theinum in 2010 under natural conditions (Altai Republic) and in cultivation (forest zone of Western Siberia). In 2017, H. theinum and H. flavescens were studied under cultivation in the forest-steppe zone of Western Siberia. The research method was based on the spectrophotometric measurement of the optical density in protein substrate (BAPA) decomposition products under the effect of trypsin (at 405 nm). Bovine trypsin manufactured by ISNBiomedical (USA) was used. BAPA (Na -benzoyl-DL-argininep-nitroanilide) served as a substrate.Conclusions. The TIA values in the flowering phase of seasonal plant development reached their maximum only under favorable conditions: in Altai Republic for the leaves of H. theinum, and in the foreststeppe zone of Western Siberia for H. flavescens. TIA values in H. theinum did not increase during flowering in the forest zone of Western Siberia and significantly decreased in the forest steppe. In view of these findings, these two species may be recommended for practical utilization in this phase of seasonal development.